Proposta de um plano estruturado de ação para atenuação de perdas não técnicas de distribuição de energia elétrica em uma empresa do Rio Grande do Sul - Bernardes, Marcelo Leandro (Universidade do Vale do Rio do Sinos, 2010)
This research turns to the study of non-technical losses in electricity distribution, aimed at proposing a structured plan of action to reduce the problem from a method that combines the approaches of Systems Thinking and Planning Scenarios(PSPC) and Thinking Process of the Theory of Constraints (PP TOC). To do so, will be adopted action research, through the stages of exploration, deep research, action and evaluation. The theoretical framework necessary for carrying out the research addresses the issues non-technical losses of electricity, Systems Thinking, Planning Scenarios, PSPC Method and Thinking Process of the Theory of Constraints. The plan of action obtained results from a comprehensive view of reality studied and a structured approach to the mitigation of non-technical losses to the context discussed. The actions were analyzed and the evaluation of the results achieved by the research was conducted qualitatively through interviews with three distinct audiences: the multidisciplinary team involved in
Keywords: pensamento sistêmico; pesquisa-ação; planejamento por cenários; processo de pensamento da teoria das restrições; perdas não técnicas de energia elétrica; action research; planning scenarios; systems thinking; thinking process of the theory of constraints; non-technical losses of electricity; Engenharias